Where truth lies : digital culture and documentary media after 9/11 - Fallon, Kris, 1976- (University of California Press, 2019)
"This boldly original book traces the evolution of documentary film and photography as they migrated onto digital platforms during the first decades of the twenty-first century. Kris Fallon brings together the emergence of several key media forms--social networking and crowdsourcing, video games and virtual environments, big data and data visualization--and demonstrates the formative influence of political conflict and the documentary film tradition on their evolution and cultural integration. Fallon argues that the ideological rifts of the period inspired the adoption and adaptation of newly available technologies toward social mobilization and political action, a role played for much of the last century by independent documentary film. By focusing on particular moments of political rupture where prior forms of representation and persuasion were discarded or discredited, Fallon asserts that "truth" now lies in a new set of media forms and discursive practices, standards that implicitly shape the documentation of everything from widespread cultural spectacles like wars and presidential elections to more invisible or isolated phenomena like the Abu Ghraib torture scandal or the "fake news" debates of 2016. Positioning documentary film and digital media side by side in the political sphere, this work deeply engages with both contemporary and historical precedents"--Provided by publisher.